(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Solitary fibrous tumor is an uncommon mesenchymal neoplasm that very rarely appears in extra serosal soft tissue. Though pleural solitary fibrous tumor is more common, up to one third of the reported cases were at extra pleural sites. Although pleural and extrapleural solitary fibrous tumors are regarded as indolent tumors, there is some evidence that extrapleural subgroup could be a subset of more aggressive malignant tumors. Accurate preoperative diagnosis of extrapleural solitary fibrous tumor is very difficult and usually is a diagnosis of exclusion. Surgical excision is mandatory and is the best therapeutic option. In this article we report a case of solitary fibrous tumor of the chest wall in a 2 months old boy. J. Paediatr. Surg. Bangladesh 4(1): 28-31, 2013 (January)